2019
DOI: 10.6004/jnccn.2019.7332
|View full text |Cite
|
Sign up to set email alerts
|

Subdivision of M1 Stage for De Novo Metastatic Breast Cancer to Better Predict Prognosis and Response to Primary Tumor Surgery

Abstract: Background: Patients with de novo metastatic breast cancer (MBC) constitute a heterogeneous group with different clinicopathologic characteristics and survival outcomes. Despite controversy regarding its prognostic value, primary tumor surgery may improve survival for selected patients. Patients and Methods: Patients with de novo MBC were identified using the SEER database and were then divided randomly into training and validation sets. A Fine-Gray competing risks model was developed to identify the variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(39 reference statements)
2
14
0
Order By: Relevance
“…In our study, age over 65 was found to be an independent predictor of worse BCSM (HR, 1.671; p < .0001). Moreover, our study consolidates the notion [21, 22] that involvement of brain or liver is an independent prognostic factor for stage IV breast cancer. In multivariate analysis, brain or liver metastasis indicated worse BCSM (HR, 2.115, 1.574; p < .0001, p = .002, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…In our study, age over 65 was found to be an independent predictor of worse BCSM (HR, 1.671; p < .0001). Moreover, our study consolidates the notion [21, 22] that involvement of brain or liver is an independent prognostic factor for stage IV breast cancer. In multivariate analysis, brain or liver metastasis indicated worse BCSM (HR, 2.115, 1.574; p < .0001, p = .002, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…The current study indicated that apart from patients with bone and brain metastasis, patients of other metastatic patterns might benefit from surgery. Likewise in a subdivision analysis of M1 patients, preferred prognosis was seen across all subdivisions after surgery except M1c category which is defined as brain involvement or multiple visceral metastasis ( 42 ). When it comes to molecular subtype, previous studies showed less benefit of surgery in metastatic triple-negative breast cancer (TNBC) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study suggests that LRT may benefit a select group of patients with indolent disease. Going along with the goal to specify which subset of stage IV disease would benefit the most from LRT, Lin et al 13 in 2019 describes the idea of subdivision of M1 stage to better predict prognosis and response to LRT. It is well-known that patients with de novo stage IV BC express heterogeneity with different clinicopathologic and prognostic factors.…”
Section: Retrospective Studiesmentioning
confidence: 99%